Individual Traits of Metric Organization in Mozart’s Compositions for Chamber Ensemble: Graphics in the Scores and the Sound Image - Pechyonkina, Svetlana O. (Music Scholarship / Problemy Muzykal’noj Nauki, 2013)
The article is devoted to the individual features in terms of rhythm and meter in Mozart’s chamber music, which are examined from the positions of meter changes during the course of the composition. The author of the article presents a short overview of existent literature from outside of Russia on this issue, where she singles outs two main trends in the examination of metrical manipulations. The first one includes the changes of meters on the borders of the respective sections of the forms (as a rule, between the primary and subsidiary theme groups), while the second one focuses on meter changes at the initial periods of various forms. The author highlights several more types of metric combinations in Mozart’s string quartets: combination of the respective meters with the different quantity of beats of measures (duple and triple measures), superimposition of the various meters on each other, as well as metric polyphony. Keywords: musical rhythm and meter, Mozart’s string quartets, metrical polyphony